Living Constitution in Indonesia: The Study of Constitutional Changes Without A Formal Amendment - Muhammad Addi Fauzani; Nur Aqmarina Deladetama; Muhammad Basrun; Muhammad Khoirul Anam (University of Jember, 2020)
The discussion regarding the living constitution in Indonesia has been increasingly important. The importance of this discussion deals with to the extent it has developed, particularly after Indonesia's constitutional amendment from 1999 to 2002. The current study of constitutional change in Indonesia, as a result of the constitutional amendment during Reformation, adds an emphasis on its change without a formal amendment. Thus, this paper will discuss the urgency of enforcing the amended 1945 Constitution in the lens of the living constitution and how to uphold it through the living constitution. This study uses doctrinal research and, in examining the case, it uses the statutory and conceptual approaches. The result of the study shows that the urgency of upholding the constitution through the living constitution relies on the concept of the living constitution that can dynamize the 1945 Constitution. In response to difficulties to formally amend the 1945 Constitution that depends on political will and rigid juridical condition, there should be a shift in the method of interpretation of the constitution by the Constitutional Court judges, from originalism to the living constitution. The enforcement of the 1945 Constitution through the living constitution can apply the constitutional convention and the interpretation by constitutional judges. This study suggests that the Government and the House of Representatives and other relevant state institutions can use the living constitution, by taking into account the constitutional convention is a source in the organization of the state to patch up the weaknesses of the constitution. Keywords: Living Constitution, Constitutional Changes, Formal Amendment.